TensorFlow Lite Solution for running ML on-device - Warden, Pete; Garg, Nupur (O'Reilly Media, Inc., 2020)
Pete Warden and Nupur Garg (Google) take you through TensorFlow Lite, TensorFlow's lightweight cross-platform solution for mobile and embedded devices. It enables on-device machine learning inference with low latency, high performance, and a small binary size. It's the standard solution at Google and the primary inference framework for all on-device use cases. Prerequisite knowledge Familiarity with ML What you'll learn Learn how TensorFlow Lite tools work and how to convert and optimize models for mobile and embedded devices.